The association between HDL‐C and stroke in the middle‐aged and elderly: A cross‐sectional study - Yang Hu; Min Song; Dongmei Wu; Yuqing Zhang; Gongbo Li; Haiyan Luo (Brain and Behavior, 2023)
Abstract Background Previous epidemiological studies have indicated that high‐density lipoprotein cholesterol (HDL‐C) is inversely associated with the risk of cardiovascular disease. However, this issue has aroused controversy in recent years. Besides, the relationship between HDL‐C and the risk of total stroke in sex and race is less clear. Thus, we aimed to examine the association between different ranges of HDL‐C and the risk of total stroke in adults over 40 years old. Methods This cross‐sectional study was conducted on a sample of 8643 participants (4222 men and 4421 women) aged ≥40 years old from the National Health and Nutrition Examination Survey 2007–2016. HDL‐C was an independent variable and stroke was a dependent variable in this study, with the other variables as potential effect modifiers. To examine the associations between them, we used multivariate logistical regression models and smooth curve fittings, as well as subgroup analyses. Results HDL‐C was inversely associated with stroke when HDL‐C was less than 1.55 mmol/L (odds ratio [OR] = 0.36, 95% confidence interval [CI] :0.21–0.62, p < .05). However, above 1.55 mmol/L, the incidence of stroke was not significant (OR = 1.29, 95% CI: 0.79–2.09, p>.05). Stratified by race/ethnicity and sex, the subgroup analyses demonstrated that HDL‐C was inversely associated with stroke in men and Whites, but no significant differences among women, Mexicans, blacks, and other races. Conclusion We found a nonlinear relationship between HDL‐C and total stroke. Our study reveals a range of inverse associations between HDL‐C and stroke (HDL‐C<1.55 mmol/L), especially among men and Whites. This finding suggested that maintaining an appropriate HDL‐C range may be beneficial in reducing the incidence of stroke.